Pemanfaatan Media Pembelajaran Qawaid Di Pondok Pesantren Sulawesi Selatan Dalam Perspektif Positivisme Auguste Comte - Agung, Nur; Jamil, Husnaini; Takdir, Takdir; Sardiyanah, Sardiyanah; AR, Amran (Universitas Islam Ahmad Dahlan Sinjai, 2025)
Qawa’id is one of the elements of the Arabic language that plays an important role in the success of language users when communicating, both orally and in writing, especially for foreign speakers. In several pesantren (Islamic boarding schools) in South Sulawesi, it has been found that the teaching of qawa’id is not supported by the use of adequate learning media, relying only on blackboards and certain textbooks. However, when examined through the lens of Auguste Comte's positivist philosophy, teaching that is not systematically measurable and does not originate from empirical experiences that are scientific cannot be classified as achieving objective knowledge. This research uses a descriptive qualitative approach aimed at finding a correlation between field facts and existing theories.